PIRATA: A Sustained Observing System for Tropical Atlantic Climate Research and Forecasting. Issue 4 (10th April 2019) - Bourlès, Bernard; Araujo, Moacyr; McPhaden, Michael J.; Brandt, Peter; Foltz, Gregory R.; Lumpkin, Rick; Giordani, Hervé; Hernandez, Fabrice; Lefèvre, Nathalie; Nobre, Paulo; Campos, Edmo; Saravanan, Ramalingam; et al.
Abstract: Prediction and Research Moored Array in the Tropical Atlantic (PIRATA) is a multinational program initiated in 1997 in the tropical Atlantic to improve our understanding and ability to predict ocean‐atmosphere variability. PIRATA consists of a network of moored buoys providing meteorological and oceanographic data transmitted in real time to address fundamental scientific questions as well as societal needs. The network is maintained through dedicated yearly cruises, which allow for extensive complementary shipboard measurements and provide platforms for deployment of other components of the Tropical Atlantic Observing System. This paper describes network enhancements, scientific accomplishments and successes obtained from the last 10 years of observations, and additional results enabled by cooperation with other national and international programs. Capacity building activities and the role of PIRATA in a future Tropical Atlantic Observing System that is presently being optimized are also described. Plain Language Summary: Long data records are essential for improving our understanding of the weather and climate, their variability and predictability, and how the climate may change in the future in response to anthropogenic greenhouse gas emissions. Climate variability in the tropical Atlantic Ocean has strong impacts on the coastal climate in particular and, consequently, the economies of the surrounding regions. Since 1997, the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA) program has maintained a network of moored buoys in the tropical Atlantic in order to provide instantaneous high‐quality data to research scientists and weather forecasters around the world. This paper describes PIRATA successes in terms of scientific discoveries and observing technology enhancements. Perspectives are also provided on PIRATA's role in the future Tropical Atlantic Observing System, currently under design, that will consist of a variety of coordinated measurements from satellites, ships, buoys, and other ocean technologies. Key Points: We describe the sustained tropical Atlantic observing system PIRATA maintained through a multinational cooperative program in ocean science Major scientific results and accomplishments obtained from the last 10 years are presented The potential role of PIRATA in a future Tropical Atlantic Observing System is described